3C.07: ARE THE PHYSICIANS RELUCTANT TO PRACTICE TELEMEDICINE IN HYPERTENSION?. (June 2015) - Sublet, M. Lopez; Courand, P.Y.; Bally, S.; Krummel, T.; Dimitrov, Y.; Brucker, M.; Coz, S. Regnier-Le; Dourmap-Collas, C.; Mourad, J.J.; Steichen, O.; Ott, J.; Barone-Rochette, G.; et al.
Abstract : Objective: The high number of patients with uncontrolled hypertension is still a public health pattern. The e-health contains all electronic health services used in order to improve communication between all the different actors. In arterial hypertension, few data exists on the possibilities: 1/ for patients to easily e-transfer their results of home blood pressure measurement (HBPM); 2/ for practitioners to receive and assess these HBPM results. Furthermore, physician's reluctance is often reported as a constraint for telemedicine development. Thus, we aimed to collect data on technical equipment of physicians, and on their expectations about this new way of relationship. Design and method: 57 physicians, hypertension specialists (36 ± 8 years old, 56% men, mostly (88%) hospital practitioners) completed a self-administered questionnaire. Results: The prevalence of technical equipment is summarized in Table 1. 77.1% of physicians thought that telemedicine could improve the control of hypertension, 29.8% thought they could provide less frequent consultations to their patients and 24.5 % that HBPM information would contribute to the fight against inertia. 83.2% of physicians would agree that HBPM data be transferred to a non- medical staff, a nurse in most cases (59.5%). Finally, while 89.5% of physicians declared they support the development of telemedicine in their daily practice, 100% of them found 3 kinds of "limits" to this exchange method. The main obstacles were: budget (49%), lack of legal frame (43%), medical reluctance (42%), difficulties in accessing or in mastering informatics tool (38.5%), confidentiality (28%), absence of direct benefit (21%), patient reluctance (21%). Figure. No caption available. Conclusions: The equipment of physicians in home or mobile devices appears no longer an obstacle for the development of a program dedicated to telemedicine. The majority of medical practitioners working in specialized hypertension department agreed with Internet e-transfer of HBPM data, including paramedics. However, all physicians highlighted various obstacles to its expansion: technical support, lack of legal frame, and financial limits.